Renewable Assignments: Comparing Faculty and Student Perceptions - Julie Lazzara; Matthew Bloom; Virginia Clinton-Lisell (Open Praxis)
This study examined faculty and student perceptions of renewable assignments within an OER-enabled pedagogy framework. Building on Wiley and Hilton’s (2018) framework, this study focused on the subset of practices that result in renewable assignments. Renewable assignments leverage OER permissions (reuse, redistribute, retain, remix, revise) to produce student work with value beyond the classroom. The study compared college students’ (N = 24) perceptions of value, interest, motivation, and reward for renewable assignments versus those of the instructor (N = 1) in one online class. Students reported that the value, interest, motivation, and reward of the renewable assignment were somewhat better than traditional assignments. However, the professor viewed the renewable assignment as more rewarding than the students did. In open-ended responses, students indicated that the benefits of the renewable assignment were enhanced motivation and the development of teamwork skills. However, students also indicated that the drawbacks of the renewable assignment were challenges with their group and that the project was lengthy and complicated. Overall, students and the instructor recognized the potential value of renewable assignments as well as their challenges. Recommendations include highlighting the importance of careful design and clear communication when implementing such assignments.